Teaching the Bible at the Heart of the Conflict: Can the Bible Teach Peace ? - Neuhaus, David M. (Proche-Orient chrétien, 2025)
David Neuhaus SJ examines the challenge of teaching the Bible as a source of peace amid the Israeli-Palestinian conflict. He condemns the use of biblical texts to justify division, discrimination, and violence, drawing on his experiences with Nazi antisemitism, apartheid, and the Israeli conflict. Despite these abuses, he asserts that the Bible can convey justice and peace. He advocates reading texts within their canonical context, with Christ's resurrection as the interpretive key, while acknowledging diverse perspectives, including Jewish ones. He emphasizes the need for a reading sensitive to current socio-political realities, echoing Patriarch Michel Sabbah's call for Palestinians to reclaim their sacred texts. Interpretation should be based on Church social teaching and international law to resolve conflicts. Lastly, Neuhaus urges discerning the sacred spirit of the text to ensure it teaches justice, peace, freedom, and equality, rejecting any ideological misuse.